The power of exercise: buffering the effect of chronic stress on telomere length. - Eli Puterman (Public Library of Science (PLoS), 2010)
Background Chronic psychological stress is associated with detrimental effects on physical health, and may operate in part through accelerated cell aging, as indexed by shorter telomeres at the ends of chromosomes. However, not all people under stress have distinctly short telomeres, and we examined whether exercise can serve a stress-buffering function. We predicted that chronic stress would be related to short telomere length (TL) in sedentary individuals, whereas in those who exercise, stress would not have measurable effects on telomere shortening. Methodology and principal findings 63 healthy post-menopausal women underwent a fasting morning blood draw for whole blood TL analysis by a quantitative polymerase chain reaction method. Participants completed the Perceived Stress Scale (Cohen et al., 1983), and for three successive days reported daily minutes of vigorous activity. Participants were categorized into two groups-sedentary and active (those getting Centers for Disease Control-recommended daily amount of activity). The likelihood of having short versus long telomeres was calculated as a function of stress and exercise group, covarying age, BMI and education. Logistic regression analyses revealed a significant moderating effect of exercise. As predicted, among non-exercisers a one unit increase in the Perceived Stress Scale was related to a 15-fold increase in the odds of having short telomeres (p<.05), whereas in exercisers, perceived stress appears to be unrelated to TL (B = -.59, SE = .78, p = .45). Discussion Vigorous physical activity appears to protect those experiencing high stress by buffering its relationship with TL. We propose pathways through which physical activity acts to buffer stress effects.